1999
DOI: 10.1002/1531-8257(199901)14:1<69::aid-mds1013>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Planning and executing an action in Parkinson's disease

Abstract: We evaluated the possible impairment in planning and executing an action in patients with Parkinson's disease (PD). The action considered in the present study was formed by two successive motor acts: reaching‐grasping an object (first target) and placing it on a second target of the same shape and size. We examined the effects of extrinsic properties of the second target (that is, distance) on the various kinematic phases of reaching‐grasping movements. Distance, position, and size of both stimuli were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Importantly, Alexander and Crutcher (1990), who recorded cell activity in the arm representation neurons of the MC, SMA, and putamen while monkeys performed a step-tracking task, reported that the preparatory neuronal activity was perturbation nonspecific, suggesting that this network was engaged in a general plan selection process. This is consistent with other reports attributing the basal ganglia network in part to a role in building and selecting action plans (Gentilucci and Negrotti 1999;Jueptner and Weiller 1998;Kimura et al 2003;Menon et al 2000).…”
Section: Neural Interactions Underlying Arbitrary Visuomotor Associatsupporting
confidence: 93%
“…Importantly, Alexander and Crutcher (1990), who recorded cell activity in the arm representation neurons of the MC, SMA, and putamen while monkeys performed a step-tracking task, reported that the preparatory neuronal activity was perturbation nonspecific, suggesting that this network was engaged in a general plan selection process. This is consistent with other reports attributing the basal ganglia network in part to a role in building and selecting action plans (Gentilucci and Negrotti 1999;Jueptner and Weiller 1998;Kimura et al 2003;Menon et al 2000).…”
Section: Neural Interactions Underlying Arbitrary Visuomotor Associatsupporting
confidence: 93%
“…However, slowness of movement can not be ascribed to a common pathogenetic mechanism in ET and PD. The prolongation of goal-directed movements in PD, labelled as bradykinesia, was shown to be due to slowness of all periods within a ballistic movement including the acceleration phase [14], whereas the delay in movement time noted in patients with ET is confined to the terminal periods of the movement where tremor is most pronounced especially in the presence of kinetic tremor [13]. This finding shows that the slowness of movement may be due to different pathophysiological mechanisms and it can not be labeled as bradykinesia in disorders such as ET and cerebellar disease.…”
Section: Discussionmentioning
confidence: 99%
“…The study also does not discuss the movement planning aspect of SMC. Gentilucci et al 44 have discussed the deficit among PD patients in retrieving the already generated motor plan. However, it does not investigate the deficit in generating or correcting the motor plan.…”
Section: Discussionmentioning
confidence: 99%